2016
DOI: 10.1021/acsami.6b08882
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Dual Character of Sulfur Atoms on Sensitizers in Dye-Sensitized Solar Cells

Abstract: Cyclometalated ruthenium sensitizers have been synthesized that differ with number of thiophene units on the auxiliary ligands. Sensitizers possessing four (SA25, SA246, and SA285) or none (SA282) sulfur atoms in their structures, were tested in solar cell devices employing I 3 − /I − redox mediator, enabling an estimation of the influence of sulfur− iodine/iodide interactions on dye-sensitized solar cell (DSC) performance. Power conversion efficiencies over 6% under simulated AM 1.5 illumination (1 Sun) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
3
9
0
Order By: Relevance
“…Thus, we hypothesize that the lower efficiency recorded for 1-SO-based DSSCs could result from a combination of two main factors: (1) a lower photocurrent, mostly related to the lower amount of 1-SO dye adsorbed on TiO 2 compared to DF15; (2) an enhanced recombination of the injected electrons to the electrolyte, resulting from attractive sulfur-iodine interactions increasing iodine concentration in the vicinity of the mesoporous oxide, possibly causing the lower photovoltage. We note that such an interaction was already invoked to explain the different performances (and in particular the lower V oc ) provided by DSSC dyes bearing sulfurcontaining heterocycles vs. sulfur-free ones, [49] as well as when comparing the results obtained with dyes having thioalkyl chains on their donor groups instead of more typical oxoalkyl substituents. [50,51] If large enough, such effects could be able to overcome the positive influence exerted by the red-shifted light absorption of dye 1-SO on TiO 2 compared to DF15 (Figure 5c).…”
Section: Photovoltaic Characterizationmentioning
confidence: 86%
“…Thus, we hypothesize that the lower efficiency recorded for 1-SO-based DSSCs could result from a combination of two main factors: (1) a lower photocurrent, mostly related to the lower amount of 1-SO dye adsorbed on TiO 2 compared to DF15; (2) an enhanced recombination of the injected electrons to the electrolyte, resulting from attractive sulfur-iodine interactions increasing iodine concentration in the vicinity of the mesoporous oxide, possibly causing the lower photovoltage. We note that such an interaction was already invoked to explain the different performances (and in particular the lower V oc ) provided by DSSC dyes bearing sulfurcontaining heterocycles vs. sulfur-free ones, [49] as well as when comparing the results obtained with dyes having thioalkyl chains on their donor groups instead of more typical oxoalkyl substituents. [50,51] If large enough, such effects could be able to overcome the positive influence exerted by the red-shifted light absorption of dye 1-SO on TiO 2 compared to DF15 (Figure 5c).…”
Section: Photovoltaic Characterizationmentioning
confidence: 86%
“…The tricarboxyterpyridine ligand was chosen to ensure that the lowest unoccupied molecular orbital (LUMO) energy of the reduced Ru II catalysts were appropriately positioned to inject electrons into TiO 2 and to anchor the catalysts to the metal oxide substrates 67 . Previous studies have shown that incorporation of chalcogen atoms in positions with access to the metal oxide surface can encourage side reactions between the electrolyte and the semiconductor 62 64 , and therefore X-Me and X-Ar were substituted para- to the ruthenium center on the central ring to direct the chalcogen atoms away from the surface. The N^C^N cyclometalating motif was chosen such that, upon oxidation, the resulting positive hole will be delocalized to encompass the central ring and its substituents, ensuring that this hole will be exposed to the solution.…”
Section: Discussionmentioning
confidence: 99%
“…In this reaction, no covalent bridge exists between the donor and acceptor, and therefore IET must be mediated by transient intermolecular contacts between the iodide donor and the catalyst molecules. It has been previously demonstrated that electron deficient chalcogens can interact with nucleophiles 59 61 , albeit quite weakly in most cases, and previous transient spectroscopic studies have demonstrated that interactions between iodide and sulfur or selenium affect the electron transfer rate constants with iodide 14 , 62 64 . For the X-Ar series, the positive hole, represented by the lowest unoccupied β-spin single electron molecular orbital (β-LUMO), of the oxidized catalyst is delocalized onto the heteroaromatic ring, but not onto the chalcogen atom itself (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Another useful take-home message is that the proper compromise between the various parameters is crucial to achieve the best cell performance, even if it is not easy to take into account all the factors which play a role in the complex processes occurring in a DSSC. Four of the aforementioned ruthenium(II) sensitizers (7b, 7c, 7d, and 7f) were published by the same group and in the same year in another paper [28], this time focusing the attention on the role of sulfur atoms in the aromatic substituents of the light-harvesting bipyridine. These moieties were different in the number of the thiophene rings and in the way they were connected: 7d had no sulfur but a fluorene-based group, 6c presented a thienothiophene, while 7b and 7f a cyclopentadieno-dithiophene unit with methyl or hexyl chains.…”
Section: Entrymentioning
confidence: 99%
“…Four of the aforementioned ruthenium(II) sensitizers (7b, 7c, 7d, and 7f) were published by the same group and in the same year in another paper [28], this time focusing the attention on the role of sulfur atoms in the aromatic substituents of the light-harvesting bipyridine. These moieties were different in the number of the thiophene rings and in the way they were connected: 7d had no sulfur but a fluorene-based group, 6c presented a thienothiophene, while 7b and 7f a cyclopentadieno-dithiophene unit with methyl or hexyl chains.…”
Section: Entrymentioning
confidence: 99%